Sri Lanka : Financial System Stability Assessment; Update, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2007)
This paper presents an update to the Financial System Stability Assessment on Sri Lanka. The paper discusses that despite a challenging macroeconomic environment characterized by a high fiscal deficit, inflationary pressures, and a widening current account, near-term risks to the financial system appear manageable. Financial soundness indicators have improved; nonetheless, stress tests suggest that banks remain relatively less resilient to interest rate and liquidity shocks. Moreover, the system faces challenges over the medium term from continued rapid credit growth, rising interest rates, and rigidities in interbank markets.